Molecular and morphological investigations on the renal mechanisms enabling euryhalinity of red stingray Hemitrygon akajei - Aburatani, Naotaka; Takagi, Wataru; Wong, Marty Kwok-Shing; Kuraku, Shigehiro; Tanegashima, Chiharu; Kadota, Mitsutaka; Saito, Kazuhiro; Godo, Waichiro; Sakamoto, Tatsuya; Hyodo, Susumu (Frontiers in Physiology, 2022)
Most cartilaginous fishes live in seawater (SW), but a few exceptional elasmobranchs (sharks and rays) are euryhaline and can acclimate to freshwater (FW) environments. The plasma of elasmobranchs is high in NaCl and urea concentrations, which constrains osmotic water loss. However, these euryhaline elasmobranchs maintain high levels of plasma NaCl and urea even when acclimating to low salinity, resulting in a strong osmotic gradient from external environment to body fluid. The kidney consequently produces a large volume of dilute urine to cope with the water influx. In the present study, we investigated the molecular mechanisms of dilute urine production in the kidney of Japanese red stingray, Hemitrygon akajei, transferred from SW to low-salinity environments. We showed that red stingray maintained high plasma NaCl and urea levels by reabsorbing more osmolytes in the kidney when transferred to low salinity. RNA-seq and qPCR analyses were conducted to identify genes involved in NaCl and urea reabsorption under the low-salinity conditions, and the upregulated gene expressions of Na+-K+-Cl- cotransporter 2 (nkcc2) and Na+/K+-ATPase (nka) were found in the FW-acclimated individuals. These upregulations occurred in the early distal tubule (EDT) in the bundle zone of the kidney, which coils around the proximal and collecting tubules to form the highly-convoluted structure of batoid nephron. Considering the previously proposed model for urea reabsorption, the upregulation of nkcc2 and nka not only causes the reabsorption of NaCl in the EDT, but potentially also supports enhanced urea reabsorption and eventually the production of dilute urine in FW-acclimated individuals. We propose advantageous characteristics of the batoid-type nephron that facilitate acclimation to a wide range of salinities, which might have allowed the batoids to expand their habitats.